2012
DOI: 10.1002/app.38322
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, antifungal activity, and mechanism of chitosan/TiO2 hybrid film against bipolaris maydis

Abstract: A chitosan/TiO 2 hybrid film, as a powerful antifungal material for controlling southern corn leaf blight, which is caused by the fungus Bipolaris maydis (B. maydis), was prepared and characterized. Its antifungal activity toward B. maydis was studied, and the experimental results indicate that it had multiple attractive antifungal properties as follows: (1) it displayed strong antifungal activity against B. maydis, with an inhibition ratio of 100% under both visible-light irradiation and in a dark environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Among the photocatalysts, TiO 2 has received considerable attention due to its good chemical stability, nontoxicity, low cost, high photocatalytic activity, and antibacterial property . The photocatalytic property of TiO 2 generates highly reactive radical with a highly oxidative and reactive nature under UV‐light irradiation can completely decompose the contaminants and also kills the microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the photocatalysts, TiO 2 has received considerable attention due to its good chemical stability, nontoxicity, low cost, high photocatalytic activity, and antibacterial property . The photocatalytic property of TiO 2 generates highly reactive radical with a highly oxidative and reactive nature under UV‐light irradiation can completely decompose the contaminants and also kills the microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.5 (a,b) indicate the zeta potential of TiO 2 NPs and CS/TiO 2 nanocomposite prepared by chemical method. The zeta potential of TiO 2 NPs was found to be -21.6 mV as the pH of dispersion medium (distilled water) is higher than that pH at PZC of TiO 2 NPs [29]. It was found that the zeta potential of TiO 2 NPs was shifted to +2.73 mV after the chemical reaction with CS.…”
Section: Morphologymentioning
confidence: 95%
“…As shown in Fig.1, at solution pH values lower than that of pH at PZC, TiO 2 NPs surface has positive charge, whereas at solution pH values higher than pH at PZC, the surface of TiO 2 NPs becomes negatively charged. This is described by equations, (1) and (2) [29].…”
Section: Preparation Of Cs/tio 2 Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan is a partially deacetylated chitin that has been shown to possess a wide spectrum of antibacterial activity [ 21 , 22 ]. Chitosan’s antimicrobial mechanisms include increasing the permeability of the microbial wall or chelation trace metals [ 23 , 24 ]. Gelatin is derived from type I collagen composed of glycine- and proline-rich repeating units [ 25 27 ].…”
Section: Different Types Of Nanoantibiotics and The Promise Of Stimulmentioning
confidence: 99%